The Influence Of Leadership Style And Work Motivation On Employee Performance In The Banten Regional Office Of The Ministry Of Law And Human Rights - Amarulla, Emiel (Sean Institute, 2024)
This research aims to find out 1) To determine the magnitude of the influence of leadership style on employee performance at the Banten Regional Office of the Ministry of Law and Human Rights. 2) To determine the magnitude of the influence of work motivation on employee performance at the Banten Regional Office of the Ministry of Law and Human Rights. 3) To determine the magnitude of the influence of leadership style and work motivation together on employee performance at the Banten Regional Office of the Ministry of Law and Human Rights. The research method used is a quantitative method. The population in this study were employees of the Banten Regional Office of the Ministry of Law and Human Rights. The technique used was total sampling, the population was 97 people, and the sample size was 133 people. Testing in this research uses SPSS. The research results show that 1) there is a significant influence between Leadership Style on Employee Performance in the Banten Regional Office of the Ministry of Law and Human Rights, with a determination of 16.1%. 2) There is no significant influence between Work Motivation on Employee Performance in the Banten Regional Office of the Ministry of Law and Human Rights with a determination of 9.4%. 3) There is an influence of Leadership Style and Work Motivation on Employee Performance in the Banten Regional Office of the Ministry of Law and Human Rights with a determination of 18.3%.